Modeling and Analysis of a Screw Fitting Assembly Process Involving a Cast Magnesium Component - Salomonsson, Kent; Svoboda, Ales; Andersson, Nils-Eric; Jarfors, Anders E. W. (Frontiers in Materials, 2020)
A finite element analysis of a complex assembly was made. The material description used was a physically based material model with dislocation density as an internal state variable. This analysis showed the importance of the materials’ behavior in the process as there is discrepancy between the bolt head contact pressure and the internals state of the materials where the assembly process allows for recovery. The end state is governed by both the tightening process and the thermal history and strongly influenced by the thermal expansion of the AZ91D alloy.